The Relationship Between Parenting Patterns and Adolescents' Learning Interests in the Online Learning Process During the Covid-19 Pandemic - Aini Nurazizah; Windarwati, Heni Dwi; Ningrum, Evi Harwiati; Wulandari, Shenda Maulina (PT Saintek Medika Nusantara, 2025)
The COVID-19 pandemic has impacted the education sector, leading to the adoption of online learning through various applications. Online learning can affect learning interest, which can cause boredom in adolescents. Parenting patterns influence the sustainability of the online learning process, especially in children's interest and motivation in forming learning habits. This study aims to determine the relationship between parenting patterns and adolescent learning interest in the online learning process amidst the COVID-19 pandemic. The research methodology employed in this study is a correlational analysis survey using a cross-sectional approach, and the sample was selected using simple random sampling. The study involved 93 respondents, including parents and adolescents aged 13-18 years, from Wirokerten Village, Banguntapan District, Bantul Regency, the Special Region of Yogyakarta. The research data analysis used the eta correlation test and was interpreted using the Pearson correlation coefficient scale. The study findings revealed a weak relationship between the two variables, with the eta correlation test results ranging from 0.213 to 0.261. In conclusion, this study affirms the existence of a relationship between parenting patterns and adolescents' learning interests in the online learning process during the COVID-19 pandemic. It is suggested that future researchers focus on exploring factors that influence parenting patterns, such as cultural and environmental factors, in the psychological development of adolescents. Additionally, analyzing cross-data between parenting patterns and psychological factors, as well as considering the perspectives of both parents and children, could provide valuable insights for further research.